Availability and potential for expansion of agricultural land in Indonesia - Nor Isnaeni Dwi Arista; Annisa Dhienar Alifia; Husni Mubarok; I Made Satria Dwi Arta; Dian Novira Rizva; Abiet Ilham Wicaksono (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Land is a critical factor in agriculture, especially in soil-based cultivation. The prevailing problem in agricultural land use that is yet to be solved is the rapid conversion to non-agricultural use, which raised concern for agriculture’s existence in the future. Moreover, the population continues to grow despite the receding agricultural land to produce food. Therefore, research and policies are starting to lean towards optimization of marginal land for agricultural activities. Indonesia still has potential marginal land for agricultural expansion. This paper uses secondary data and former studies to summarize the potential and availability of marginal land for agricultural expansion based on the land categories: forest land, dryland, and wetland (tidal swamp and peat). This paper also discusses the government's extensification program and the results of its implementation. We found that various reports about marginal lands utilization emphasized optimizing the target land with appropriate agricultural technology. The presentation of data obtained through literature studies can strengthen the opinion that the potential availability and potential for expansion of agricultural land in Indonesia is real. This paper is expected to provide a comprehensive reference for all Indonesian regional governments, so stakeholders continue optimizing the potential of existing natural resources.